Effect of OH⁻ Doping on the Dielectric Properties of Amorphous Ta₂O₅ Thin Films: A Combined First-Principles Calculations and Experimental Study - Zhao, Jiping; Li, Shiyu; Guo, Yeting; Zhao, Yuhan; Xu, Jingsong; Li, Yanling; Xu, Youlong (Electrochimica acta, 2026)
•OH⁻ doping creates localized metallic states in amorphous Ta₂O₅, initiating dielectric breakdown.•Higher electrolyte pH increases leakage current by ∼4.5 times and degrades dielectric properties.•Elevated pH promotes OH⁻ incorporation and crystallization, leading to extensive electrical treeing.•Controlling electrolyte pH is crucial for enhancing the reliability of solid-state tantalum capacitors. The pH value of the electrolyte during anodic oxidation exerts a complex influence on the dielectric properties of amorphous Ta₂O₅ films. However, the underlying atomic-scale mechanism remains poorly understood. Combining experimental characterization with first-principles calculations, this study elucidates that OH⁻ doping introduces additional density of states near the Fermi level, leading to localized metallic behavior within the Ta₂O₅ dielectric layer. With increasing electrolyte pH, severe electrical treeing and crystallization occur, resulting in an approximately 4.5-fold increase in leakage current and significant dielectric failure. Spectral and microstructural analyses confirm enhanced incorporation of OH⁻ and intensified crystallization under high-pH conditions. Computational results further demonstrate that doped OH⁻ species act as electron emission centers under high electric fields, initiating dielectric breakdown. These findings provide profound insights into the field-induced degradation mechanism in amorphous dielectric materials and underscore the critical importance of controlling electrolyte pH to enhance the reliability of solid-state tantalum capacitors. [Display omitted]